Seismic spectrograms of an anelastic layer with different source-receivers configurations - Ayman N Qadrouh, José M Carcione, Ahmed MA Salim, Zuhar Zahir Tu, . (2016)
Thin and relatively thin anelastic layers (compared to the signal wavelength) generally represent hydrocarbon reservoirs, where the rock is a sandstone or a source rock saturated with brine, oil and gas. The study of the seismic response of these layers is important to detect the hydrocarbons on the basis of the reflection and transmission coefficients and the wave velocity and attenuation properties